2021
DOI: 10.1056/nejmoa2106356
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance or Discontinuation of Antidepressants in Primary Care

Abstract: BACKGROUNDPatients with depression who are treated in primary care practices may receive antidepressants for prolonged periods. Data are limited on the effects of maintaining or discontinuing antidepressant therapy in this setting. METHODSWe conducted a randomized, double-blind trial involving adults who were being treated in 150 general practices in the United Kingdom. All the patients had a history of at least two depressive episodes or had been taking antidepressants for 2 years or longer and felt well enou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
126
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(133 citation statements)
references
References 26 publications
3
126
0
4
Order By: Relevance
“…Although many patients do not want long-term treatment with antidepressants [11], there is an increasing trend for them to be maintained on antidepressants for two years or more [12,13], and the use of antidepressants has greatly increased over the last three decades [14]. Although pharmacogenetics may hold promise for personalizing antidepressant treatments [15,16], it is becoming increasingly common that antidepressants are prescribed indefinitely for all patients with a history of previous relapses, to mitigate the risks of chronic illness and relapse [11,12,17,18]. This is despite evidence of the waning effectiveness of medications over time [19][20][21][22], and even increased risk of relapse and other harmful outcomes for those remaining on medications after several years [17,23].…”
Section: Introductionmentioning
confidence: 99%
“…Although many patients do not want long-term treatment with antidepressants [11], there is an increasing trend for them to be maintained on antidepressants for two years or more [12,13], and the use of antidepressants has greatly increased over the last three decades [14]. Although pharmacogenetics may hold promise for personalizing antidepressant treatments [15,16], it is becoming increasingly common that antidepressants are prescribed indefinitely for all patients with a history of previous relapses, to mitigate the risks of chronic illness and relapse [11,12,17,18]. This is despite evidence of the waning effectiveness of medications over time [19][20][21][22], and even increased risk of relapse and other harmful outcomes for those remaining on medications after several years [17,23].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanistic outcomes are not reported in the report or in the main trial paper that reports the clinical outcomes; they will be reported in separate paper(s). 34 However, we provide their description below.…”
Section: Mechanistic Outcomesmentioning
confidence: 99%
“…Equally pressing is the need for more evidence and guidance on how best to withdraw inappropriate medication (deprescribing) 1314. Clinical trials have already shown that it is safe and even beneficial for patients to stop some long term drugs such as antidepressants and statins towards the end of life 1516…”
mentioning
confidence: 99%